2016
DOI: 10.1155/2016/4703168
|View full text |Cite
|
Sign up to set email alerts
|

Planetary Sciences, Geodynamics, Impacts, Mass Extinctions, and Evolution: Developments and Interconnections

Abstract: Research frontiers in geophysics are being expanded, with development of new fields resulting from technological advances such as the Earth observation satellite network, global positioning system, high pressure-temperature physics, tomographic methods, and big data computing. Planetary missions and enhanced exoplanets detection capabilities, with discovery of a wide range of exoplanets and multiple systems, have renewed attention to models of planetary system formation and planet’s characteristics, Earth’s in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…the time of deposition and is thus considered a distal section (e.g., Goderis et al, 2013;Urrutia-Fucugauchi and Pérez-Cruz, 2016); it is thought to represent a paleo-deposition depth of~600-1000 m (Alegret and Thomas, 2013;Smit, 1990), an upper-middle-bathyal environment similar to or slightly shallower than that proposed for the nearby Caravaca site.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…the time of deposition and is thus considered a distal section (e.g., Goderis et al, 2013;Urrutia-Fucugauchi and Pérez-Cruz, 2016); it is thought to represent a paleo-deposition depth of~600-1000 m (Alegret and Thomas, 2013;Smit, 1990), an upper-middle-bathyal environment similar to or slightly shallower than that proposed for the nearby Caravaca site.…”
Section: Geological Settingmentioning
confidence: 99%
“…The technique therefore allows high-resolution analyses within layers of sub-mm thickness, as is the case for the KPgB at distal sections (Urrutia-Fucugauchi and Pérez-Cruz, 2016). This boundary, dated at 66.04 ± 0.02 Ma (Renne et al, 2013), has been widely studied (Goderis et al, 2013;Schulte et al, 2010), and its link to a meteorite impact broadly demonstrated (Alvarez et al, 1980;Schulte et al, 2010;Smit and Hertogen, 1980).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major geochemical anomalies, recognized worldwide, characterize this boundary in both marine and continental depositional environments (Goderis et al, 2013). However, the extraterrestrial contribution is particularly evident in the ejecta layer of marine distal sites, those located more than 5000 km from the Chicxulub impact crater (Claeys et al, 2002;Goderis et al, 2013;Smit, 1999;Urrutia-Fucugauchi and Pérez-Cruz, 2016). The Agost (SE Spain) section is one of the best exposed and most representative of marine distal areas for the KPgB event (Molina et al, 2005;Rodríguez-Tovar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The plate is moving between 2 to 5 centimetres per year (Abu Bakar, Jamaluddin, Omar, & Razak, 2013). According to Urrutia-Fucugauchi and Perez-Cruz (2016) plate tectonics is a global lithosphere separated by several plates moving on relative motion.…”
Section: Introductionmentioning
confidence: 99%